A new species of the genus Vandellia (Linderniaceae) from Thailand - Sutthisaksopon, Phanom; Chantaranothai, Pranom; Simpson, David A. (Phytotaxa, 2014)
Vandellia yamazakii, a new species of Linderniaceae from western Thailand, is described and illustrated.